Box–Behnken response surface methodology for optimization of operational parameters of compression ignition engine fuelled with a blend of diesel, biodiesel and diethyl ether. Issue 2 (3rd March 2016) - Patel, Paresh D.; Lakdawala, Absar; Patel, Rajesh N.
Abstract : The response surface method is adopted to express the output parameter (brake thermal efficiency) as a function of engine parameters including compression ratio (CR), injection pressure (IP) and injection timing (IT). The range of engine parameters selected is: 16 ≤ CR ≤ 18; 180 ≤ IP ≤ 220 bar; 15° ≤ IT ≤ 25 0 BTDC. It is shown that the proposed Box–Behnken design required only 15 runs of experiments for the response surface between output parameters and engine parameters. Using 'Design Expert' software, 2D and 3D plots are generated. Such plots give an idea of domination of process variables and exhibit the trend of interaction between the variables. Moreover, a statistical significant test (ANOVA) is carried out to develop a 'Regression Model'. The results of ANOVA suggested that the proposed 'Regression Model' is best fit with Standard Deviation of 0.093, Adjusted R 2 of 0.9619 and Adequate Precision of 19.686. Further the validation of 'Regression Model' is carried out by comparing the predicated values of thermal efficiency with that of experimental observations. The comparison suggested that the model is robust enough to predict thermal efficiency of the CI engine over a wide range of operating conditions with error less than 1%. Finally an optimum combination of engine parameters i.e. CR = 18, IP = 220 bar and IT = 20 0 before top dead centre is proposed.